2012
DOI: 10.1155/2012/973927
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Standardized ROS Production Profile in Humans by Electron Paramagnetic Resonance

Abstract: Despite the growing interest in the role of reactive oxygen species (ROS) in health and disease, reliable quantitative noninvasive methods for the assessment of oxidative stress in humans are still lacking. EPR technique, coupled to a specific spin probe (CMH: 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine) is here presented as the method of choice to gain a direct measurement of ROS in biological fluids and tissues. The study aimed at demonstrating that, differently from currently available “a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 41 publications
9
78
0
Order By: Relevance
“…EPR spectroscopy is the only direct and obvious method for detection and measurement of free radicals. EPR spectroscopy can be used to directly study free radicals in the blood and tissues 19,20 or in vitro antioxidant study of natural antioxidants. 21,22 Previously, we reported that the liver and kidneys appear to be the major organs of QD deposition after intravenous administration and that QDs can undergo degradation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…EPR spectroscopy is the only direct and obvious method for detection and measurement of free radicals. EPR spectroscopy can be used to directly study free radicals in the blood and tissues 19,20 or in vitro antioxidant study of natural antioxidants. 21,22 Previously, we reported that the liver and kidneys appear to be the major organs of QD deposition after intravenous administration and that QDs can undergo degradation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…; Mrakic‐Sposta et al. ). Addition of oxygen‐sensitive label (NOX‐15.1–5 μ mol/L) to the blood sample allows us to monitor oxygen concentrations and cellular as well as mitochondrial oxygen consumption (Bobko et al.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous methods have been employed for the assessment of XO inhibitory potency of various purine and nonpurine analogs in vitro and in vivo. Apart from the traditional approaches that include measurement of enzymatic reaction products, ROS level, hydrogen peroxide production, uric acid measurement, involving biochemical array, UV, fluorescence, etc. There are many other direct and indirect assessment techniques such as oxygen consumption .…”
Section: Xanthine Oxidasementioning
confidence: 99%